Coaching in higher education - Campayo Muñoz, Emilia Ángeles (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This study aims to respond to the difficulty noted by the students who are studying the Master Degree in Early Childhood Education to develop their Final Degree Project (FDP). To do this, a coaching experience is described with the objective of introducing higher education teachers to this methodology as a tool for innovation and educational improvement within the framework of the FDP tutoring of the aforementioned degree. Finally, the positive and improving aspects of the implementation described are discussed and the need to promote this kind of methodology among higher education teachers is considered.